Profile of Personality and Psychopathology Dimensions of Indonesian Medical Students who Failed in Medical Doctor Competency Exams (UKMPPD) - Patricia Wulandari; Rachmat Hidayat; Carla R Marchira (HM Publisher, 2020)
Introduction: Medical doctor competency exams (UKMPPD) in Indonesia is a final test that should be followed by medical student before being declared worthy of a medical doctor’s degree. This exam is certainly intended with good intentions, in order to improve the standards and quality of graduates of Indonesian doctors. However, each policy turns out to have two opposite sides of the situation, on the one hand it is profitable but on the other it often creates new problems. Students’ fear of the competency test often causes new psychological problems for students. No doubt the failure of the competency exam causes students to experience prolonged disappointment and sadness, which in turn will cause depression. This research is the first research that aim to present a description of personality and psychopathology dimension data from UKMPPD participants who failed the test. Method: This study was an exploratory descriptive study by presenting narratives of personality and psychopathology dimensions of unsuccessful UKMPPD participants. This research was conducted at the Faculty of Medicine, Universitas Sriwijaya Palembang, Indonesia. Each participant was assessed personality and psychopathology dimensions using MMPI-2 (Minnesota Multiaxial Personality Inventory-2). The results of analysis with MMPI-2 present data in the form of clinical psychic conditions, the work capacity, interpersonal relationships, the work abilities and the ability to change the self potential of the research subjects. Result: The research subjects were UKMPPD participants who did not successfully pass the first exam. From 7research subjects, there were 2 subjects who successfully passed the second exam (28.5%) and there were 3 people who successfully passed after the third exam (43%). Meanwhile, 2 research subjects have not successfully passed the UKMPPD exam until the fifth exam (28.5%). The results are quite surprising that of the 7 participants who failed to pass the UKMPPD exam, all of them felt depression. Conclusion: Medical students who experienced UKMPPD failures have an inability to develop their own potential which result in depression due to failure of the exam